1995
DOI: 10.1128/mcb.15.2.1005
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-Independent Repression of AP-1-Inducible Collagenase Promoter Activity by Glucocorticoid Receptors

Abstract: The role of the ligand in glucocorticoid receptor-mediated transactivation and transrepression of gene expression was investigated. Half-maximal transactivation of a mouse mammary tumor virus-chloramphenicol acetyltransferase reporter gene in transfected cells expressing the human glucocorticoid receptor mutant GRL753F, from which the rate of ligand dissociation is four to five times higher than the rate of dissociation from normal receptors, required a 200-to 300-fold-higher concentration of dexamethasone tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 75 publications
1
33
0
Order By: Relevance
“…In these model systems, it is necessary that at ®rst, ligand binds with its receptor to stimulate receptor activation, and next, the activated receptor complex be dissociated from hsp90, and then nuclear translocation be occurred. However, the recent report showed that GR-dependent transrepression of AP-1 was ligandindependent, which was observed in transfected cells after heat shock in the absence of ligand (Liu et al, 1995). In particular, the action mechanism of glucocorticoid hormone to inhibit the transcription of collagenases has been suggested by nuclear translocation of GR and its interfering the AP-1, the main After treatment with 10 mM of UA, 10 mM of Dexa or 10 mM of RU486 for 3 or 6 days, the cells were harvested and nuclear proteins (20 mg) were fractionated and transferred to Hybond-ECL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In these model systems, it is necessary that at ®rst, ligand binds with its receptor to stimulate receptor activation, and next, the activated receptor complex be dissociated from hsp90, and then nuclear translocation be occurred. However, the recent report showed that GR-dependent transrepression of AP-1 was ligandindependent, which was observed in transfected cells after heat shock in the absence of ligand (Liu et al, 1995). In particular, the action mechanism of glucocorticoid hormone to inhibit the transcription of collagenases has been suggested by nuclear translocation of GR and its interfering the AP-1, the main After treatment with 10 mM of UA, 10 mM of Dexa or 10 mM of RU486 for 3 or 6 days, the cells were harvested and nuclear proteins (20 mg) were fractionated and transferred to Hybond-ECL.…”
Section: Discussionmentioning
confidence: 98%
“…Dexa activates and translocates GR from cytosol to nucleus by dissociating it from hsp90. The translocated GR inhibits the activity of AP-1 by directly binding to it (Jonat et al, 1990;Nicolson et al, 1990;SchuÈ le et al, 1990;Liu et al, 1995). MMP-9 has the AP-1 binding sequences on the promoter region .…”
Section: Discussionmentioning
confidence: 99%
“…In other GR heterozygous T-ALL systems, that is, CCRF-CEM cells with the L753F mutation that impairs ligand binding, 21 basal GR expression and/or auto-induction of the wild-type allele have been implicated in GC sensitivity. 4,22 To compare these parameters in the two human T-ALL systems, we first exploited 'real time' RT-PCR to quantitate GR expression prior to, and 12 h after, GC exposure at the mRNA level in GC-sensitive CCRF-CEM-C7H2 (phenotype GR L753F/wt ), 16 GC-resistant CEM-C1 (same phenotype GR L753F/wt ) 22 and Jurkat (phenotype GR R477H/wt ) T-ALL cells.…”
Section: Gc-resistant Jurkat and Cem-c1 Cells Express Less Basal Gr Tmentioning
confidence: 99%
“…19 More specifically, CCRF-CEM cells, perhaps the best studied model for GC-induced apoptosis in human ALL, carry a GR gene mutation (L753F) on one allele that has already occurred in vivo 20 and markedly impairs ligand binding. 21 GC-resistant CCRF-CEM derivatives (mostly established by selection in GC-containing media) have either acquired loss-of-function mutations in the GR gene of the second allele, [13][14][15][16] have reduced basal GR levels 22 and/or fail to sufficiently auto-induce their functional GR gene upon GC exposure. 4 To gain further insights into the mechanism of GC resistance in leukemic cells, we investigated a different GCresistant T-ALL model, that is, the human T-ALL cell line Jurkat which is widely used in apoptosis research and has been exploited as a model for the molecular analysis of GR mutants.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant RU486-liganded GR is efficiently imported into the nucleus but manifests a generalized defect in transcriptional activation. Nevertheless, this form of activated GR remains sufficient for transcriptional repression in certain cell systems and promoter contexts (45)(46)(47). Dexamethasone, a pure glucocorticoid agonist, inhibited IGF-I-stimulated activation of p70 S6K in a dose-related fashion within 4 h of exposure to the steroid (Fig.…”
Section: Resultsmentioning
confidence: 99%